2020
DOI: 10.3390/cancers12102752
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Pace of Tumor Progression as Assessed by Serial 18F-FDG PET/CT Scan and Liquid Biopsy in Refractory Colorectal Cancer: The CORIOLAN Trial

Abstract: Introduction: Decision making in refractory colorectal cancer (rCRC) is challenging, with limited data available to predict patient outcome. We conducted a study to assess the pace of cancer progression as a potential prognostic and decision tool. Methods: CORIOLAN was a prospective, single-center, single-arm trial recruiting refractory CRC patients with an ECOG performance status of ≤1 and an estimated life expectancy of ≥12 weeks. 18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These studies all reported a significant correlation between baseline "high CTC" status and reduced survival. Camera et al, 2020 [17], similarly reported a prognostic difference in the presence of disease refractory to standard treatment or unresectable CRC. Coumans et al, 2012 [6], reported that survival for patients with metastatic CRC patients with CTCs is reduced by 6.6 months for each 10-fold CTC increase.…”
Section: Prognostic Thresholdsmentioning
confidence: 99%
“…These studies all reported a significant correlation between baseline "high CTC" status and reduced survival. Camera et al, 2020 [17], similarly reported a prognostic difference in the presence of disease refractory to standard treatment or unresectable CRC. Coumans et al, 2012 [6], reported that survival for patients with metastatic CRC patients with CTCs is reduced by 6.6 months for each 10-fold CTC increase.…”
Section: Prognostic Thresholdsmentioning
confidence: 99%
“…The discovery cohort included eligible patients from the CORIOLAN trial and CHRONOS & KAIROS study. The former investigated the association between the natural pace of tumor progression (as indicated by tumor metabolic changes on serial 18F-FDG PET scans) and survival in chemorefractory CRC [16]. Following a 14-day observation period without any active anti-cancer therapy, patients from this trial could be treated off-study based on local standards.…”
Section: Study Design and Eligibility Criteriamentioning
confidence: 99%
“…Likewise, predictive and prognostic relationships were found, with worse median Progressive-Free Survival (mPFS) and mOS in both patients with poor baseline CTCs (mPFS 4.5 months vs. 7.9 months; p = 0.0002; mOS 9.4 months vs. 18.5 months; p < 0.0001) and those with persistently elevated CTCs throughout treatment [73]. Another study by Camera et al, focusing on the dynamic evolution of biomarkers (cfDNA, CEA, and CTC), as well as radiological changes as prognostic factors of OS in mCRC patients, failed to show a significant association with outcomes, while only baseline elevation of such biomarkers, especially CTC, predicted worse OS (HR 6.5) [37,74].…”
Section: Metastatic Diagnosis Prognosis and Therapeutic Response Eval...mentioning
confidence: 99%